MEDICO-SOCIAL PROFILES OF PHYSICIANS IN TRAINING - Sichkoriz О.Ye. (World of Medicine and Biology, 2019)
The purpose of this paper is to develop recommendations for improving the system of postgraduate medical education in the context of the overall health care reform. The survey method implemented in the form of a standardized (formalized) interview was used as the main tool for collecting social and psychological information. We have interviewed the total of 375 internship doctors after graduation including 33.60% male responders and 66.40% female ones aged 20-34 years. The results of the questionnaire indicate that internship doctors experience such polar feelings as calmness, confidence, non-contentiousness, anxiety, worry, fear, and despair. The responders suggest that health care institutions meet current requirements incompletely. Thus, there is the necessity to significantly improve the material and technical conditions as well as to review the system of medical institutions functioning while developing the strategy of health care system reform.